2020
DOI: 10.1002/ehf2.13060
|View full text |Cite
|
Sign up to set email alerts
|

10 year trends in hospitalization rates due to heart failure and related in‐hospital mortality in Poland (2010–2019)

Abstract: Aims Heart failure (HF) remains a major public health challenge worldwide. Contemporary epidemiological data on HF hospitalization rates and related in-hospital mortality are scarce also in Poland. The aim of the study was to determine the trends in hospitalization rates due to HF and related in-hospital mortality in Poland in the recent decade. Methods and results Data on HF hospitalizations and in-hospital mortality in patients aged >17 years in Poland between 2010 and 2019 were obtained from the central dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…Before the COVID-19 outbreak, the prognosis in HF was unsatisfactory with the one year-mortality of patients after HF diagnosis estimated at 24% [ 5 ]. In-hospital mortality varied from 12% to 19%, depending on the study [ 6 ]. As our study revealed, SARS-CoV-2 infection significantly worsens in-hospital course and long-term prognosis of HF patients with three-month mortality two times higher than in HF patients without COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the COVID-19 outbreak, the prognosis in HF was unsatisfactory with the one year-mortality of patients after HF diagnosis estimated at 24% [ 5 ]. In-hospital mortality varied from 12% to 19%, depending on the study [ 6 ]. As our study revealed, SARS-CoV-2 infection significantly worsens in-hospital course and long-term prognosis of HF patients with three-month mortality two times higher than in HF patients without COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 24% of patients die within one year of HF diagnosis [ 5 ]. In-hospital mortality during HF hospitalizations is also unacceptably high and varies from 12 to 19%, depending on consecutive years, gender, and age groups [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the present data are in agreement with findings by Sierpiński et al who reported a 14% in-hospital mortality in Poland in all prevalent HF patients over a 10 year period. 15 On the other hand, they observed a gradual uptrend in in-hospital deaths between 2010 and 2019. The opposite trend in our study could result from a more recent population (dating back to 2013 vs. 2010 in Sierpiński's study) thus treated in a unified manner according to new HF recommendations that were published in 2012 and updated in 2016.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, the present data are in agreement with findings by Sierpiński et al . who reported a 14% in‐hospital mortality in Poland in all prevalent HF patients over a 10 year period 15 . On the other hand, they observed a gradual uptrend in in‐hospital deaths between 2010 and 2019.…”
Section: Discussionmentioning
confidence: 99%
“…В последние десятилетия частота госпитализаций с СН увеличилась во всем мире [9,16,17], как в течение года после установки диагноза, так и повторных госпитализаций в последующие годы, достигнув в среднем 64 событий на 100 пациенто-лет [9]. При этом ожидается, что в ближайшие 25 лет в связи с ростом численности и постарением населения число госпитализаций, связанных с СН, увеличится на 50 % [18].…”
Section: обзоры §unclassified